Una especie nueva de Echeveria (Crassulaceae) originaria del estado de Jalisco, México - García Ruiz, Ignacio; Pérez-Calix, Emmanuel (Instituto de Ecología, A.C., 2007)
Based on botanical specimens collected in the state of Jalisco, Mexico, Echeveria patriotica (Crassulaceae) is described and illustrated. Due to the possession of the following features, it is assigned to series Gibbiflorae (Baker) A. Berger: stem present, leaf blades narrowed at the base in the form of a pseudopetiole, inflorescence with more than 3 ramifications and an elongated rachis, and corolla cylindrical-urceolate more than 13 mm long. Of the species belonging to this section, E. patriotica is most similar to E. grisea E. Walther, from which it differs by having longer a pedicel, calyx and corolla. In addition, it is distinguished by the color of the flower and the nectaries.